Media politics and culture - "Gardner, Carl (ed.)" (London, 1979)
While the general understanding of communist journalism has been limited to equating its writing with dense prose and torturous jargon, the explicit focus of most studies of Marxist and communist publications has been on their political-ideological role in supporting the activities of their parent organizations, with little consideration of either the contributions of editors or texts in reaching out to the public. This essay addresses this gap in the literature by identifying important differences in editorships and house styles in Marxism Today , a periodical published by the Communist Party of Great Britain between 1957 and 1991. The differences between two editors and changes in editorial content and presentation, accessibility and writing style are analysed to assess fully Marxism Today's textual appeal to party and non-party readers, as it moved out from the radical margins into the mainstream of national political debate.
Keywords: Communication